Analysing the effect of germination on phenolics, dietary fibres, minerals and γ-amino butyric acid contents of barnyard millet (Echinochloa frumentaceae). (1st March 2016) - Sharma, Seema; Saxena, Dharmesh C.; Riar, Charanjit S.
Abstract: The purpose of this study was to optimize the germination conditions of barnyard millet variety PRJ-1 in order to enhance the availability of bioactive compounds. The results indicated that the optimized germinated barnyard millet flour presented the higher nutraceuticals content than the raw barnyard millet flour. The effect of independent variables (soaking time, germination temperature and germination time) on responses (total/individual phenolic and flavonoids contents (TP&FC), antioxidant activity (AoxA) were analysed by central composite rotatable design (CCRD) analysis using RSM optimization technique. Statistical analysis revealed that soaking time, germination time, germination temperature significantly ( P <0.05) influenced all the responses. The results indicated that with an increase in soaking and germination time as well as germination temperature, the AoxA, TPC and TFC of foxtail millet flours increased significantly. The quantitative analysis of phenolic extract of raw and optimized germinated barnyard millet by GC–MS revealed that the optimized germinated barnyard millet flour contained higher amount of Hexadecanoic acid (5.59%), Octadecadienoic acid (Z, Z) (14.59%), 9, 12 Octadecadienoic acid, ethyl ester (11.00%), c-Sitosterol (4.00%), Lupeol (5.18%), Campesterol (7.59%) as compared to raw flour. Dietary fibres (23.74 g/100 g) and minerals increased where as phytates decreased significantly due to germination. The yield of GABA extracted from germinated barnyard millet was 12.34% and that of GABA purity increased from 3.38 mg/100 to 35.70 mg/100 g. The research specifically validates the potential of germination and pays the way for utilization of minor millet in the product development and extraction of valuable compounds.